Energy Conservation in Fermentations of Anaerobic Bacteria - Buckel, Wolfgang (Frontiers in Microbiology, 2021)
Anaerobic bacteria ferment carbohydrates and amino acids to obtain energy for growth. Due to 8 the absence of oxygen and other inorganic electron acceptors, the substrate of a fermentation 9 has to serve as electron donor as well as acceptor, which results in low free energies as 10 compared to that of aerobic oxidations. Until about 10 years ago, anaerobes were thought to 11 exclusively use substrate level phosphorylation (SLP), by which only part of the available energy 12 could be conserved. Therefore, anaerobes were regarded as unproductive and inefficient 13 energy conservers. The discovery of electrochemical Na+ gradients generated by biotin- 14 dependent decarboxylations or by reduction of NAD+ with ferredoxin changed this view. 15 Reduced ferredoxin is provided by oxidative decarboxylation of 2-oxoacids and the recently 16 discovered flavin based electron bifurcation (FBEB). In this review, the two different 17 fermentation pathways of glutamate to ammonia, CO2, acetate, butyrate and H2 via 3- 18 methylaspartate or via 2-hydroxyglutarate by members of the Firmicutes are discussed as 19 prototypical examples in which all processes characteristic for fermentations occur. Though the 20 fermentations proceed on two entirely different pathways, the maximum theoretical amount of 21 ATP is conserved in each pathway. The occurrence of the 3-methylaspartate pathway in 22 clostridia from soil and the 2-hydroxyglutarate pathway in the human microbiome of the large 23 intestine is traced back to the oxygen-sensitivity of the radical enzymes. The coenzyme B12- 24 dependent glutamate mutase in the 3-methylaspartate pathway tolerates oxygen, whereas 2- 25 hydroxyglutaryl-CoA dehydratase is extremely oxygen-sensitive and can only survive in the gut, 26 where the combustion of butyrate produced by the microbiome consumes the oxygen and 27 provides a strict anaerobic environment. Examples of coenzyme B12-dependent eliminases are 28 given, which in the gut are replaced by simpler extremely oxygen sensitive glycyl radical 29 enzymes.